In the Search for a Non-Invasive Sonification Method Based on a Physically-Based Model for the Guidance of the Visually Impaired Population - Herrera Martínez, Marcelo; Useche Ramírez, Jorge E. (TECCIENCIA, 2022)
The present paper initially presents to the reader the most prominent results in the field of SSD (Sensory Substitution Devices) for the visually impaired population. Afterwards, a technical-ergonomic comparison is held, where some important academic and commercial projects in the last decade are highlighted. Several transcendental discoveries in this matter are depicted and at the end a new promising method is introduced, making use of Haralick texture features. The main finding of the present work is that this approach could present to the visually impaired texture-like properties of the image based on its physical characteristics, and even more, since the Haralick approach is mathematically rigorous, then it may render a more coherent and congruent image-to-sound algebra than previous methods.